Modern trends in the developmend of citizenship - Balgimbekova, G.U.; Isabekova, V.S. (KSU Publ., 2017)
This article discusses one of the problems of scientific development of the Institute of citizenship in the Republic of Kazakhstan and in the countries of the former Soviet Union. Analyzes the historical background of the constitutional legal institution of citizenship at different stages of formation of the state. Perspectives of constitutional legal regulation, on the basis of historical and theoretical propositions for further improvement taking into account the constitutional and legal experience of the CIS countries. The origin and historical development of citizenship allows us to consider the development of this phenomenon in the dynamics in the Republic of Kazakhstan, in the CIS countries and other foreign countries and to determine prospects for further development of citizenship. In the article the conception of citizenship associated with the emergence of the ancient state in the form of a slave Republic, developing in the framework of the Western type state, with all that define this type of state characteristics.
Азаматтық институты дамуының заманауи беталысы
Современные тенденции развития института гражданства
Keywords: the institution of citizenship; human rights; government; law; national independence; development; structure; situation